Some indices of meat and meat products quality and safety - Кіт, А. А.; Михайлютенко, С. М.; Кручиненко, О. В.; Євстаф’єва, В. О.; Мельничук, В. В. (Scientific Progress & Innovations, 2018)
Environmental, feed, and food products pollution with mycotoxins and pesticides creates the potential threat for animal and human health, leads to economic losses as a result of diseases and mortality of farm animals and poultry. Product samples were selected (for making laboratory analyses, expert examination, testing) during the fair conducted by the Municipal enterprise «City Shop» in Kyiv. Meat and meat products were the objects of analyses. The testing was held in the Regional government laboratory of the Government Food Product Consumer Service in Kyiv and Kyiv region. Sample selection was made according to the «Order of selecting product samples of animal, plant, and biotechnological origin for making analyses dated June 14, 2002 №833», according to Article 14 of the Law of Ukraine «About the foundations of government supervision (control) in the sphere of economic activities», and according to the Decision №126 dated 29.11.2017. The content of aflatoxin B1 was checked in the samples. The mentioned toxin belongs to the most toxic natural hepato-carcinogens among all the compounds and also pesticides. It was established that AFB1 level was less than 0,0144 mg/kg. Also the meat and meat product samples were analyzed as to the content of such pesticides as hexachlorane (gamma-isomer), dichlorodiphenyl, trichloromethyl-methane and its metabolites, bazudin, carbophos, metaphos, chlorophos, and dichlorovinyl-diphosphate. It was found out that meat and meat products corresponded to the standard requirements as to quality and safety indices (concerning pesticides and mycotoxins) and were allowed to selling. The monitoring system of the residual amounts of polluting substances remains the guarantor of product safety in Ukraine. It is the systematic control of aflatoxins and pesticides in farm products that will ensure human and animal health. It should be noted that to eliminate the risks of danger, it is necessary to improve the system of monitoring raw products, which are used for manufacturing food products concerning safety indices at all the stages of producing, selling, and storing.